2009
DOI: 10.3354/dao02151
|View full text |Cite
|
Sign up to set email alerts
|

Integration of hydrodynamics into a statistical model on the spread of pancreas disease (PD) in salmon farming

Abstract: Pancreas disease (PD) is an emerging disease in salmon farming caused by the salmonid alphavirus (SAV). SAV is evidently spread horizontally between neighbouring salmon farms, but whether such transmission occurs by passive drift in the water current or via fomites is not known. We tested whether hydrodynamic modelling contributes to explain the spread of PD, in which case SAV is likely to spread by passive drift. We present a simple logistic regression model that accounts for the effect of PD in the neighbour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 17 publications
(25 reference statements)
1
52
0
Order By: Relevance
“…Gustafson et al (2007) showed that tidal currents affected the spread of ISA in the Quoddy region of Atlantic USA and Canada. Viljugrein et al (2009) concluded that the spread of PD in an area on the west coast of Norway was significantly better predicted by using hydrodynamic modelling to estimate water contact between farm sites, than by simply using distance between farm sites.…”
Section: Open Production Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gustafson et al (2007) showed that tidal currents affected the spread of ISA in the Quoddy region of Atlantic USA and Canada. Viljugrein et al (2009) concluded that the spread of PD in an area on the west coast of Norway was significantly better predicted by using hydrodynamic modelling to estimate water contact between farm sites, than by simply using distance between farm sites.…”
Section: Open Production Unitsmentioning
confidence: 99%
“…In parallel, increasing efforts are put into hydrodynamic modelling along the Norwegian coast. Hydrodynamic models used to estimate reciprocal relative water contact between local salmon farm sites, have also been integrated with statistical models on disease spread (Viljugrein et al, 2009). The integration of…”
Section: Modelling Disease Spread In Salmon Farmingmentioning
confidence: 99%
“…Although microparasites tend to be more short-lived, they can also be transported considerable distances by seawater movement, for example, spread between salmon farms of infectious salmon anemia (Gustafson et al 2007) and pancreas disease (Viljugrein et al 2009) outbreaks follow the directions of currents predicted using hydrodynamic modeling. Infection pressure, however, likely declines rapidly with distance from source population.…”
Section: Empirical Evidence For Thresholdsmentioning
confidence: 99%
“…Microprasites are primarily viruses, bacteria, and protists, which typically replicate within an individual host, spread by host-to-host contact, and do not have an obligate free-living stage in the life cycle (May & Anderson 1991), although aquatic microparasites may also be transported by water movement (Gustafson et al 2007, Viljugrein et al 2009). The dynamics of a microparasitic disease can be modeled by dividing the host population into classes according to their infection status, such as susceptible, infected, or recovered (SIR) (May & Anderson 1991, Grenfell & Dobson 1995.…”
Section: Host Density Thresholds For Microparasitesmentioning
confidence: 99%
“…Experimental work has shown that SAV can survive for ~6 d at 10°C in sterile saltwater with organic loading (Graham et al 2007). This suggests that the virus is sufficiently viable in the aquatic environment to be useful for modelling, as assumed by Viljugrein et al (2009). Phylogenetic data of SAV subtype IV are consistent with a history of repeated transmission between dab and salmon.…”
Section: Mitigating Factors and Spillbackmentioning
confidence: 57%